Pengaruh Relaksasi Otot Progresif terhadap Kelelahan pada Pasien yang Menjalani Terapi Hemodialisa - Purwanto, Erwin; Maryadi, Maryadi; Sartika, Sartika; Ayun R. Yusuf, Nur (Mando Care Jurnal, 2025)
Fatigue is one of the most common complaints experienced by patients with chronic kidney disease undergoing hemodialysis. This condition is chronic and recurrent and can reduce the patient's ability to perform daily activities. One way to manage fatigue is through progressive muscle relaxation therapy. This study aimed to determine the effect of progressive muscle relaxation therapy on fatigue levels in patients with chronic kidney disease undergoing hemodialysis. This study used a pre-experimental design with a one-group pre-post test design. The sample size was 24 respondents. Fatigue levels were measured using the Numeric Rating Scale-Fatigue (NRS-F) before and after the intervention. The results showed a decrease in the average fatigue score from 5.00 before the intervention to 3.00 after the intervention, with a p-value of 0.041 (<0.05), indicating a significant difference before and after progressive muscle relaxation therapy. conclusion, progressive muscle relaxation therapy has been proven effective in reducing fatigue levels in patients with chronic kidney disease undergoing hemodialysis.